Secretome-Wide Analysis of Lysine Acetylation in Fusarium oxysporum f. sp. lycopersici Provides Novel Insights Into Infection-Related Proteins - Li, Jingtao; Gao, Mingming; Gabriel, Dean W.; Liang, Wenxing; Song, Limin (Frontiers in Microbiology, 2020)
Fusarium oxysporum f. sp. lycopersici (Fol) is the causal agent of Fusarium wilt disease in tomato. Proteins secreted by this pathogen during initial host colonization largely determine the outcome of pathogen-host interactions. Lysine acetylation (Kac) plays a vital role in the functions of many proteins, but little is known about Kac in Fol secreted proteins. In this study, we analyzed lysine acetylation of the entire Fol secretome. Using high affinity enrichment of Kac peptides and LC-MS/MS analysis, 50 potentially secreted Fol proteins were identified and acetylation sites determined. Bioinformatics analysis revealed 32 proteins with canonical N-terminal signal peptide leaders, and most of them were predicted to be enzymes involved in a variety of biological processes and metabolic pathways. Remarkably, all 32 predicted secreted proteins were novel and encoded on the core chromosomes rather than on the previously identified LS pathogenicity chromosomes. Homolog scanning of the secreted proteins among 40 different species revealed 4 proteins that were species specific, 3 proteins that were class-specific in the Ascomycota phylum, and 25 proteins that were more widely conserved genes. These secreted proteins provide a starting resource for investigating putative novel pathogenic genes, with 26 up-regulated genes encoding Kac proteins that may play an important role during initial symptomless infection stages.